Precalculus: Concepts Through Functions, A Unit Circle Approach to Trigonometry (3rd Edition)

Published by Pearson
ISBN 10: 0-32193-104-1
ISBN 13: 978-0-32193-104-7

Chapter 11 - Sequences; Induction; the Binomial Theorem - Section 11.1 Sequences - 11.1 Assess Your Understanding - Page 827: 31



Work Step by Step

We notice the pattern of the sequence that the sequence starts from $-1$ and then alternates the sign at each new term. So, we determine the pattern as: $$\{a_n\}=(-1)^{n+1}$$ Thus, we have $a_1=(-1)^{1+1}=(-1)^2=1$, $a_2=(-1)^{2+1}=(-1)^3=-1$, etc.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.